Searching locally and globally: Applying Daniel Levinthal’s scholarship to international business - Pedersen, Torben; Larsen, Marcus M; Dasí, Àngels (Journal of International Business Studies, 2020)
Daniel A. Levinthal has made several important contributions to the fields of strategy and management. His research has been pivotal in enhancing our understanding of interactions between the internal and external contexts that organizations face as well as the roles of experience, search, and learning processes. Despite substantial overlap between the core issues in international business (IB) and Levinthal’s work, the IB field has yet to fully embrace key tenets of his research. We aim to bridge this gap by providing a number of concrete suggestions for areas in which IB research may benefit from Levinthal’s work and vice versa.